Criminality in the microfinance sector: a symptom of “broken window” - Akonor, Edgar Takyi (UCC Law Journal, 2022)
The phenomenal rate of deviant acts in the microfinance sector of Ghana’s economy has generated a great deal of debate about its ramifications for the future of the sector and financial inclusion efforts. The Sustainable Development Goals (SDGs) target 16:4 acknowledges the dangers syndicated crimes pose to the attainment of the goals and proposes a reduction in all forms of illicit financial flows and organized crime by 2030. In this paper, it is argued that one of the major effects of criminality in the microfinance sector is the deepening of financial exclusion of people who are already on the fringes of the financial inclusion bracket. Semi-structured and in-depth interview guides were used to collect data for the study. The Broken Window theory of criminology was adopted as the theoretical framework to guide the study. The study found that criminal and fraudulent activities in the microfinance sector are real issues that need attention. The study concludes that the laxity and delays on the part of state institutions mandated to regulate the sector and their inability to crack the whip on criminal elements in the sector have contributed to the festering of crimes in the sector and its resultant financial exclusion. The study recommends that regulatory agencies should develop and deploy stringent monitoring and surveillance regime in order to forestall the occurrence of criminal activities which have plagued the sector.